Determination of tetrodotoxin (TTX) levels in various tissues of the silver cheeked puffer fish (Lagocephalus sceleratus (Gmelin, 1789)) in Northern Cyprus Sea (Eastern Mediterranean). (February 2020) - Akbora, Hasan Deniz; Kunter, İmge; Erçeti̇n, Tuğba; Elagöz, Ali Murat; Çi̇çek, Burak Ali
Abstract: Lagocephalus sceleratus from the family Tetraodontidae, which is originated from the Red Sea, started to migrate to Mediterranean waters after the opening of the Suez Channel in 1869. Since they do not have any predators in the Mediterranean Sea, their population increased in number very fast. Different tissues of L. sceleratus have tetrodotoxin (TTX). TTX is a non-protein, heat resistant molecule which binds to voltage-gated sodium channels of musculatory and nervous system. Ingestion of the fish can cause a wide variety of effects from mild toxications to death. This study is the first toxicity report of L. sceleratus for Cyprus. Due to the lack of data on toxicity levels of L. sceleratus, and some cases of poising after the ingestion of the fish were the reasons for the start of this work. 24 L. sceleratus were sampled from 3 different areas to represent Northern Cyprus, during one year period. 16 fish samples selected and grouped into 4 fishes per season for toxicity assay. TTX levels from liver, gonad, intestine, muscle and skin tissue homogenate were analyzed with TTX ELISA. Totally 80 tissues were analyzed, 40% of them were above the toxic limit (2.2 μg/g). Most toxic tissue, according to the seasonal average, was found in the summer season and was determined as; Liver = 13.48 μg/g. Most toxic three fishes were found to be female with a length of 45–60 cm. TTX distribution among tissues have similarities with previously published studies from different regions. Highlights: This is the first study from Cyprus that focuses on the tetrodotoxin levels of Lagocephalus sceleratus. 21% of the stomach contents are composed of fishers' gear. 60% of the tissues analyzed in this study were found above the toxic limit in the spawning season. Out of the spawning season, 3/4 of the toxic fish were found to be female.